2023
DOI: 10.1136/gutjnl-2022-328408
|View full text |Cite
|
Sign up to set email alerts
|

NNMT enriches for AQP5+cancer stem cells to drive malignant progression in early gastric cardia adenocarcinoma

Abstract: ObjectiveEarly gastric cardia adenocarcinoma (EGCA) is a highly heterogeneous cancer, and the understanding of its classification and malignant progression is limited. This study explored the cellular and molecular heterogeneity in EGCA using single-cell RNA sequencing (scRNA-seq).DesignscRNA-seq was conducted on 95 551 cells from endoscopic biopsies of low-grade intraepithelial neoplasia, well/moderately/poorly differentiated EGCA and their paired adjacent nonmalignant biopsy samples. Large-scale clinical sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Functionally, NNMT is a metabolic enzyme that transfers S-adenosyl-L-methionine to nicotinamide to generate S-adenosyl homocysteine and 1-methyl nicotinamide, allowing NNMT to fine-tune the methylation status of cancer cells (figure 1). 11 Consistent with an epigenetic role for NNMT, Wang et al 10 found that NNMT overexpression reduced H3K27me3 repressive histone mark levels at the CTNNB1 (encoding β-catenin) and WNT5A promoter regions. This resulted in increased CTNNB1 expression, enhanced β-catenin binding to the AQP5 promoter, and activation of AQP5 transcription to maintain AQP5 + CSCs.…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…Functionally, NNMT is a metabolic enzyme that transfers S-adenosyl-L-methionine to nicotinamide to generate S-adenosyl homocysteine and 1-methyl nicotinamide, allowing NNMT to fine-tune the methylation status of cancer cells (figure 1). 11 Consistent with an epigenetic role for NNMT, Wang et al 10 found that NNMT overexpression reduced H3K27me3 repressive histone mark levels at the CTNNB1 (encoding β-catenin) and WNT5A promoter regions. This resulted in increased CTNNB1 expression, enhanced β-catenin binding to the AQP5 promoter, and activation of AQP5 transcription to maintain AQP5 + CSCs.…”
mentioning
confidence: 86%
“…The NAPRT-mediated NAD synthesis pathway is termed the Preiss-Handler pathway. see Wang et al 10 for details. NAAD, nicotinic acid adenine dinucleotide; NAMN, nicotinic acid mononucleotide; NAMPT, nicotinamide phosphoribosyltransferase; NAPRT, nicotinate phosphoribosyltransferase; SAH, S-adenosyl homocysteine; SAM, S-adenosyl-L-methionine.…”
mentioning
confidence: 99%
See 3 more Smart Citations